‘Men And Women Under A Shroud Of Silence’ : Silence In Nadia Sebkhi’s Les Sanglots De Césarée (مجلة الواحات للبحوث والدراسات, 2020)
This article attempts to explain the forms, meanings, and roles of silence in Nadia Sebkhi’s novel Les Sanglots de Césarée. The analysis of characters, typographical blanks, reticence, aposiopesis, and ellipses reveals that the novel is an example of literature of silence. The article is divided into four sections. The first section offers a definition of silence in linguistics and literature while the second explores mute and silent characters in the selected text. The third section explores the figures and forms of silence in Sebkhi’s novel. The analysis ends with a conclusion that confirms that both silence and speech are eloquent.Keywords - literary silence, blanks, ellipsis, suspensivity, Algerian literature